Analysis of Corneal Spherical Aberrations in Chinese Bilateral Ectopia Lentis Patients - Chen, Jiahui; Tang, Yating; Jing, Qinghe; Lu, Yi; Jiang, Yongxiang (Frontiers in Medicine, 2021)
Purpose: To analyze the anterior, posterior, and total corneal spherical aberrations (ASA, PSA, & TSA) in Chinese bilateral ectopia lentis (EL) patients. Methods: A cross-sectional study was conducted to evaluate corneal spherical aberrations (CSA) using a Pentacam system at the 6-mm optical zone. Axial length, keratometry, astigmatism, corneal asphericity were also determined. Results: This study included 247 patients (420 eyes) with a mean age of 18.1 years. The values of ASA, PSA, and TSA were 0.136 ± 0.100μm, −0.118 ± 0.030μm, and 0.095 ± 0.095μm, respectively. In the EL patients with Marfan syndrome (MFS), ASA and TSA were significantly lower than in the non-MFS patients (0.126 ± 0.094μm vs. 0.155 ± 0.107μm, P = 0.004 for ASA; 0.085 ± 0.091μm vs. 0.114 ± 0.099μm, P = 0.003 for TSA), whereas PSA was not significantly different (P = 0.061). The values of ASA and TSA were significantly higher in the EL patients aged ≥ 40 years old than in younger patients, whereas ASA and PSA were lower in patients aged < 10 years old than in older patients (all P < 0.05). In the multiple linear regression analysis, age, keratometry, astigmatism, anterior asphericity, HOA, and LOA were positively or negatively correlated with TSA in the EL patients (r = 0.681, P < 0.001). Conclusions: CSA was low in the EL patients especially for MFS and tended to increase with aging. Preoperatively individual measurement of spherical aberrations was necessary in bilateral EL patients with MFS.